Repurposing the Strontium Ranelate Antiosteoporotic Drug as a New Outstanding Biocompatible Blue Dye - Luca M. Sihn; Erick L. Bastos; Marcelo Nakamura; Mayara K. Uchiyama; Henrique E. Toma (Colorants, 2023)
Blue dyes are relatively uncommon in nature, and a novel dithiophene dye (RanB) is reported in this paper. This dye is derived from an old anti-osteoporotic drug and is a metal ion complexing agent, displaying a planar molecular structure, with two sets of carboxylate, isonitrile, thiophene, and iminodiacetate groups. The blue color originates from a strong absorption peak at 648 nm, accompanied by an unusual fluorescence at 555 nm, with higher energy compared to the main absorption band. RanB forms complexes with lanthanoid ions through the iminodiacetate groups and serves as an effective sensitizer for Tb3+ ions, heightening their emission and improving their use as luminescent agents. Its photo-physical properties and the interaction with Tb3+ have been investigated using absorption spectroscopy, steady-state and time-resolved fluorescence spectroscopy, along with computational methods (ZINDO/S and DFT). The RanB toxicity in human umbilical vein endothelial cells has also been tested, showing a lack of toxicity, holding promising prospects for application as a luminescent and coloring agent in pharmaceuticals and food.